Physical Exercise Exacerbates Acute Kidney Injury Induced by LPS via Toll-Like Receptor 4 - Húngaro, Talita Guerreiro Rodrigues; Freitas-Lima, Leandro Ceotto; Gregnani, Marcos Fernandes; Perilhão, Mauro Sérgio; Alves-Silva, Thaís; Arruda, Adriano Cleis; Barrera-Chimal, Jonatan; Estrela, Gabriel Rufino; Araújo, Ronaldo Carvalho (Frontiers in Physiology, 2020)
Introduction: Lipopolysaccharide (LPS) is a systemic response-triggering endotoxin, which has the kidney as one of its first targets, thus causing acute injuries to this organ. Physical exercise is capable of promoting physiological alterations and modulating inflammatory responses in the infectious process through multiple parameters, including the toll-like receptor (TLR)-4 pathway, which is the main LPS signaling in sepsis. Additionally, previous studies have shown that physical exercise can be both a protector factor and an aggravating factor for some kidney diseases. This study aims at analyzing whether physical exercise before the induction of LPS endotoxemia can protect kidneys from acute kidney injury. Methods: C57BL/6J male mice, 12 weeks old, were distributed into four groups: (1) sedentary (control, N = 7); (2) sedentary + LPS (N = 7); (3) trained (N = 7); and (4) trained + LPS (N = 7). In the training groups, the animals exercised 5×/week in a treadmill, 60 min/day, for 4 weeks (60% of max. velocity). Sepsis was induced in the training group by the application of a single dose of LPS (5 mg/kg i.p.). Sedentary animals received LPS on the same day, and the non-LPS groups received a saline solution instead. All animals were euthanized 24 h after the administration of LPS or saline. Results: The groups receiving LPS presented a significant increase in serum urea (p < 0.0001) and creatinine (p < 0.001) concentration and renal gene expression of inflammatory markers, such as tumor necrosis factor alpha and interleukin-6, as well as TLRs. In addition, LPS promoted a decrease in reduced glutathione. Compared to the sedentary + LPS group, trained + LPS showed overexpression of a gene related to kidney injury (NGAL, p < 0.01) and the protein levels of LPS receptor TLR-4 (p < 0.01). Trained + LPS animals showed an expansion of the tubulointerstitial space in the kidney (p < 0.05) and a decrease in the gene expression of hepatic AOAH (p < 0.01), an enzyme involved in LPS clearance. Conclusion: In contrast to our hypothesis, training was unable to mitigate the renal inflammatory response caused by LPS. On the contrary, it seems to enhance injury by accentuating endotoxin-induced TLR-4 signaling. This effect could be partly due to the modulation of a hepatic enzyme that detoxifies LPS.